The Determination of Spot and Futures Prices with Storable Commodities - Turnovsky, Stephen J. (Econometrica, 1983)
This paper analyzes the effects of futures trading in a market for a storable commodity, in which producers and speculators are assumed to be risk averse and specifications of the aggregate supply and inventory demand functions are derived from explicit optimization. A critical aspect is how the parameters of these functions change with the introduction of the future market as it is through these induced parameter changes that the futures market exerts its influence on the spot price. The effects of the futures market on both the long-run average spot price and its variance are analyzed. While we are unable to draw any definitive conclusions on this issue, we find that in all cases considered the futures market stabilizes the spot price, as well as lowering its long-run mean. FOR MANY YEARS NOW, the question of the effects of futures trading on the stability of spot prices has been extensively debated. This topic has been discussed at various levels. For example, farmers and agricultural interest groups have claimed that futures trading destabilizes spot prices, thereby imposing welfare losses on the economy. In the United States, Congress has decided that futures trading can cause price destabilization and has subjected futures trading to the regulation of the Commodity Futures Trading Commission. At a more analytical level, economists have been investigating the issue, both empirically, and more recently, theoretically as well.